2012
DOI: 10.1111/j.1365-3040.2012.02564.x
|View full text |Cite
|
Sign up to set email alerts
|

A diminution in ascorbate oxidase activity affects carbon allocation and improves yield in tomato under water deficit

Abstract: The regulation of carbon allocation between photosynthetic source leaves and sink tissues in response to stress is an important factor controlling plant yield. Ascorbate oxidase is an apoplastic enzyme, which controls the redox state of the apoplastic ascorbate pool. RNA interference was used to decrease ascorbate oxidase activity in tomato (Solanum lycopersicum L.). Fruit yield was increased in these lines under three conditions where assimilate became limiting for wild‐type plants: when fruit trusses were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 88 publications
6
63
1
1
Order By: Relevance
“…Crucially, the ability of the plants to limit the availability of major amino acids is strongly influenced by the redox state of the apoplast. It was shown previously that low AO activities in tomato (Solanum lycopersicum) not only increased leaf sugar contents but also altered apoplastic hexose-Suc ratios (Garchery et al, 2013). Therefore, it is likely that the sugar and amino acid composition of the phloem is changed as a result of the low AO activities in tobacco leaves studied here and that this contributes to the limitation of infestation.…”
Section: Discussionmentioning
confidence: 58%
“…Crucially, the ability of the plants to limit the availability of major amino acids is strongly influenced by the redox state of the apoplast. It was shown previously that low AO activities in tomato (Solanum lycopersicum) not only increased leaf sugar contents but also altered apoplastic hexose-Suc ratios (Garchery et al, 2013). Therefore, it is likely that the sugar and amino acid composition of the phloem is changed as a result of the low AO activities in tobacco leaves studied here and that this contributes to the limitation of infestation.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to the studies of Zhang et al (2011), they silenced GDP-D-mannose-3 0 ,5 0 -epimerase, which resulted in a reduced level of ascorbic acid in the fruit (Gilbert et al 2009). Recently, Garchery and Gest (2013), using the RNAi approach, obtained transgenic lines with decreased ascorbate oxidase activity and thus the plants showed increased levels of total ascorbic acid.…”
Section: Improvement Of Fruit Qualitymentioning
confidence: 99%
“…Yamamoto et al (2005) observed that knockdown of AO led to higher tolerance to salinity and oxidative stresses in Arabidopsis (Arabidopsis thaliana). Garchery et al (2013) reported an increase in the early fruit diameter and alteration in hexose and Suc contents in leaves in AO knockdown lines in tomato (Solanum lycopersicum). These examples raise questions regarding the physiological role of AO genes in plants, since absence or lower expression of AO genes often appears to be favorable.…”
mentioning
confidence: 99%